Intra-caldera rhyolitic eruptions : lithostratigraphy and pyroclast textures to reconstruct the ~1314 CE Kaharoa eruption of Mt Tarawera, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Earth Science at Massey University, Palmerston North, New Zealand - Todde, Andrea (Massey University, 2022)
Rhyolitic eruptions are commonly sourced from silicic caldera systems and display a great variety of eruptive styles and magnitudes, ranging from the extrusion of lava domes to catastrophic caldera-forming eruptions. The different types of eruptions associated with rhyolitic volcanism can result in severe impacts to the environment and society, varying from a local to a global scale. Yet, due to their typically longer recurrence times compared to volcanic events of less evolved magmas, only a very limited number of rhyolitic eruptions have been documented in historical accounts or recorded through geophysical monitoring. This lack of direct records limits the current understanding of the main processes controlling the dynamics of rhyolitic volcanism and hinders the construction of robust eruption scenarios. This study presents new insights into the eruptive behaviour of rhyolitic eruptions using the Kaharoa eruption from the Taupō Volcanic Zone (TVZ) of New Zealand as a case study. The TVZ is one of the most frequently active regions of rhyolitic volcanism on Earth with the 1314±12 CE Kaharoa eruption being the most recent rhyolitic event in the TVZ. This eruption is sourced from multiple vents along the Tarawera dome complex, within the Okataina caldera system, and erupted up to 9 km3 of magma. By investigating the Kaharoa pyroclastic succession, this research contributes to constraining the key factors controlling the dynamics of moderate- to large-scale rhyolitic eruptions occurring in intra-caldera settings. The approach used in this research combines geological field investigations and quantification of the sedimentological and componentry characteristics of the deposits with the analyses of single-clast features (e.g., bulk density and textures of vesicles in pumice clasts). Field-stratigraphic relationships of 24 lithostratigraphic units for the Kaharoa deposit elucidate the intra-eruption chronology, placing time constraints on the numerous, discrete explosive episodes, while revaluating previous stratigraphic schemes. From variations within the stratigraphy in sedimentary structures, grain size and particle content of the pyroclastic beds, an array of deposit types is identified and linked to temporal changes in transport and depositional patterns as well as eruptive styles. Five distinct explosive eruptive phases are established for the Kaharoa eruption. These include multiple phases of repeated subplinian-type, fall-dominated episodes, alternating with phases characterised by overall sustained pyroclastic density currents and episodes of ash emission. A final sixth phase places the main lava dome building sequence within the proposed reconstruction and eruption model. Following constraints on the eruption from field-derived data, an in-depth investigation of the Kaharoa pumice microtextures is performed using Scanning Electron Microscopy, which revealed complex and anisotropic vesicle textures. To characterise the observed complex vesicle features of the Kaharoa pumices, a methodology is developed providing guidelines for the 2D quantification of tube-like vesicles. The integration and interpretation of the pumice textural results along the stratigraphic sequence indicates that the main processes that regulate the evolution of the magma during ascent in the shallow conduit region are magma shearing, bubble coalescence and outgassing. These factors provide bounding conditions for magma ascent dynamics and indicate cyclical variation in the eruption behaviour. Furthermore, by combining textural, sedimentological and componentry data, this study suggests that the inferred dike-shaped geometry of the conduit, together with conduit-vent wall instabilities, are primary factors in controlling: (i) the intrinsic responses of the magma to ascent and decompression to the surface and (ii) the characteristics of the ejected gas-pyroclasts mixtures, influencing the transportsedimentation regime. The dynamic magma-conduit interrelationships ultimately govern the changes in eruptive styles and overall dynamics of the Kaharoa eruption. This research defines a framework to relate depositional and textural characteristics to eruptive processes and provides critical insights into the types of eruptive sequence and eruptive style changes of intra-caldera rhyolitic eruptions. The scenario depicted for the Kaharoa eruption highlights the complex episodic, multi-phase, explosive to dome-forming nature of dike-fed rhyolitic eruptions. Furthermore, it provides crucial information for scenario-based volcanic hazard assessments of a Kaharoa-type eruption at Okataina and at other rhyolitic centres within the TVZ. Finally, comparing with available datasets from other volcanic events of similar magnitudes, magma composition, and geological settings, this research suggests that this type of rhyolitic eruption behaviour is common at other silicic caldera systems worldwide, making it of great relevance for future volcanic hazard studies.
Keywords: Tarawera, Mount (N.Z.); Eruption, 1314; Volcanism; Rhyolite; New Zealand; 370512 Volcanology